Case Report: Detection of a Novel Germline PALB2 Deletion in a Young Woman With Hereditary Breast Cancer: When the Patient's Phenotype History Doesn't Lie - De Angelis, Carmine; Nardelli, Carmela; Concolino, Paola; Pagliuca, Martina; Setaro, Mario; De Paolis, Elisa; De Placido, Pietro; Forestieri, Valeria; Scaglione, Giovanni Luca; Ranieri, Annalisa; Lombardo, Barbara; Pastore, Lucio; et al. (Frontiers in Oncology, 2021)
The partner and localizer of BRCA2 (PALB2) is a major BRCA2 binding partner that participates in homologous recombination repair in response to DNA double-strand breaks. Germline alterations of the PALB2 gene have recently been associated with a high risk of developing breast cancer. We investigated a 37-year-old Caucasian woman with breast cancer and a family history of breast cancer using targeted next-generation sequencing. A novel heterozygous deletion involving exons 5 and 6 was found in the PALB2 gene and resulted in the production of a truncated PALB2 protein. These findings expand the mutational spectra of PALB2-associated breast cancer and may improve the mutation-based screening and genetic diagnosis of breast cancer.